Vascular safety of erenumab for migraine prevention - Kudrow, David (Neurology, 2020)
OBJECTIVE: To examine the cardiovascular, cerebrovascular, and peripheral vascular safety of erenumab across migraine prevention studies. METHODS: Vascular adverse events (AEs) and blood pressure data were integrated across 4 double-blind, placebo-controlled studies of erenumab and their open-label extensions in patients with chronic or episodic migraine. Subgroup analyses were conducted by acute migraine-specific medication use and number of vascular risk factors at baseline. Standardized search terms were used to identify vascular AEs (cardiovascular, cerebrovascular, or peripheral). An independent committee adjudicated whether targeted events were vascular in origin. RESULTS: In placebo-controlled studies, 2,443 patients received placebo (n = 1,043), erenumab 70 mg (n = 893), or erenumab 140 mg (n = 507) subcutaneously once monthly. Regardless of acute migraine-specific medication use or vascular risk factors at baseline, AE incidence was similar across the placebo and erenumab treatment groups. Hypertension AEs were reported for 0.9% (placebo), 0.8% (erenumab 70 mg), and 0.2% (erenumab 140 mg) of patients. Vascular AEs, which were similar across double-blind and open-label treatment, generally were confounded, with plausible alternative etiologies. In 18 patients with events reviewed by the independent committee, 4 events were positively adjudicated as cardiovascular in origin: 2 deaths and 2 vascular events. All 4 positively adjudicated cardiovascular events occurred during open-label erenumab treatment. CONCLUSION: Selective blockade of the canonical calcitonin gene-related peptide receptor with erenumab for migraine prevention had a vascular safety profile comparable to that of placebo over 12 weeks, with no increased emergence of events over time. Further study of long-term safety of erenumab in patients with migraine is needed. CLINICALTRIALS.GOV IDENTIFIERS: NCT02066415, NCT02456740, NCT01952574, NCT02483585, NCT02174861, and NCT01723514. CLASSIFICATION OF EVIDENCE: This analysis provides Class II evidence that for patients with migraine, erenumab does not increase the risk of vascular AEs.